Soret-Dufour effects on MHD rotating flow of a viscoelastic fluid. Issue 2 (25th February 2014) - Hayat, T.; Naz, R.; Asghar, S.; Alsaedi, A.
Abstract : Purpose: – The purpose of this paper is to study the heat and mass transfer with Soret-Dufour effects for the magnetohydrodynamic three-dimensional flow of second grade fluid in the rotating frame of reference. Design/methodology/approach: – Series solution is obtained by homotopy analysis method. Findings: – Increase in Soret number, Schmidt number and Dufour number, the heat transfer increases and mass transfer decreases. Effects of Prandtl and Eckert numbers are qualitatively similar as they assist the temperature profile and reduce the concentration of species. Increase in the length of the channel versus height increases the temperature profile but decreases the concentration field. Increase in the second grade fluid parameter causes reduction in both the temperature and concentration fields. The heat flux values at the lower plate are smaller than the values at the upper plate, whereas the situation is opposite in the case of mass transfer. Originality/value: – These findings will be useful for the fluid flow in porous channel.